One golden summer - Fortune, Carley (New York, New York : Berkley Romance, 2025)
"Good things happen at the lake. That's what Alice's grandmother says, and it's true. Alice spent just one summer at a cottage with Nan when she was seventeen-it's where she took that photo, the one of three grinning teenagers in a yellow speedboat, the image that changed her life. Now Alice lives behind a lens. As a photographer, she's most comfortable on the sidelines, letting other people shine. Lately, though, she's been itching for something more, and when Nan falls and breaks her hip, Alice comes up with a plan for them both: another summer in that magical place, Barry's Bay. But as soon as they settle in, their peace is disrupted by the roar of a familiar yellow boat, and the man driving it. Charlie Florek was nineteen when Alice took his photo from afar. Now he's all grown up-a shameless flirt, who manages to make Nan laugh and Alice long to be seventeen again, when life was simpler, when taking pictures was just for fun. Sun-slanted days and warm nights out on the lake with Charlie are a balm for Alice's soul, but when she looks up and sees his piercing green gaze directly on her, she begins to worry for her heart. Because Alice sees people-that's why she is so good at what she does-but she's never met someone who looks and sees her right back"--
"A novel"--Cover.
Includes discussion questions.
Keywords: Summer -- Fiction; Man-woman relationships -- Fiction; Romance fiction